2021
DOI: 10.3390/foods10020425
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues and Risk Assessment from Monitoring Programs in the Largest Production Area of Leafy Vegetables in South Korea: A 15-Year Study

Abstract: : Leafy vegetables are widely consumed in South Korea, especially in the form of kimchi and namul (seasoned vegetables) and are used for wrapping meat. Therefore, the management of pesticide residues in leafy vegetables is very important. A total of 17,977 samples (49 leafy vegetables) were mainly collected in the largest production area of leafy vegetables (Gwangju Metropolitan City and Chonnam Province) in South Korea. They were analyzed within the government’s monitoring programs (Gwangju Metropolitan City)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
1
18
1
3
Order By: Relevance
“…Our ndings con rm similar ndings to other studies carried out in Poland, Nigeria and Saudi Arabia which found that many pesticides had a HQ>1 [46,65,66]. On the other hand, literature from Turkey, Poland, Ghana, China and South Korea showed no chronic health risk associated with pesticide residues in fruits and vegetables [53,54,58,60,[67][68][69][70]. using probabilistic modelling, Z Eslami, V Mahdavi and B Tajdar-Oranj [57] in Iran found that pesticide residues did not pose health risks to adults and children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our ndings con rm similar ndings to other studies carried out in Poland, Nigeria and Saudi Arabia which found that many pesticides had a HQ>1 [46,65,66]. On the other hand, literature from Turkey, Poland, Ghana, China and South Korea showed no chronic health risk associated with pesticide residues in fruits and vegetables [53,54,58,60,[67][68][69][70]. using probabilistic modelling, Z Eslami, V Mahdavi and B Tajdar-Oranj [57] in Iran found that pesticide residues did not pose health risks to adults and children.…”
Section: Discussionsupporting
confidence: 91%
“…The number of pesticides with EDIs greater than the ADI decreased with age with 18, 13, 9, 11, 8, 9, and 9 for age groups under 5 years, 5-12, 13-19, 20-25, 36-49 and 50+ years respectively. Dichlorvos had the highest risk with a HQ of 444 followed by alanycarb (314), Fonofos (68), fenitrothion (62), dioxacarb (55) and benfuracarb (24) among children under 5 with a similar trend across age groups (see supplementary table 2). Overall, HQ values decreased across age groups with children under 5 presenting highest risks and adults 50+ having the lowest chronic health risks for the nine pesticides as shown in Figure 2.…”
Section: Health Risk Assessment By Age Groupmentioning
confidence: 81%
“…The use of pesticides, if not appropriate, may lead to problems like contamination of the water, potential damage to sensitive species (e.g., bees), contamination of final food products and water, with up to 90% of applied pesticides not reaching the target species, and, also, because of the development of resistant pathogens and pests [ 39 ]. A high number of PPPs were not reauthorized (or companies did not provide the dossier for the reregistration of products out of patent, due to high costs and uncertain benefits) and leaves a gap for several uses.…”
Section: Discussionmentioning
confidence: 99%
“…In the Republic of Korea, tricyclazole has been listed as a monitored pesticides, which is required for agricultural commodities when they are imported for the first time because of the high retention frequency [37,38]. In the Republic of Korea, the maximum residue limit (MRL) of tricyclazole is set at 0.05 mg/kg for spinach, a leafy vegetable . Although the regulation of pesticide residue in soil has not been established, the possible pesticide residual concentration in soil that can produce a safe crop can be suggested based on the BCF data from this study.…”
Section: Suggested Management Concentration Of Soil Tricyclazolementioning
confidence: 99%